2003
DOI: 10.1046/j.1463-1318.2003.00524.x
|View full text |Cite
|
Sign up to set email alerts
|

Transverse coloplasty pouch and colonic J‐pouch for rectal cancer – a comparative study

Abstract: Objectives The introduction of the colonic J-pouch has markedly improved the functional outcome of restorative rectal cancer surgery. However colonic J-pouch surgery can be problematic and may present some late evacuatory problems. To overcome these limitations a novel pouch has been proposed: the transverse coloplasty pouch. The purpose of our study was to compare the functional outcomes of these two different types of pouches -the transverse coloplasty pouch (TCP) and the colonic J-pouch (CJP) -during the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
36
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 27 publications
(43 reference statements)
7
36
0
1
Order By: Relevance
“…The exit conduit from the coloplasty reservoir could fit/traverse the anal sphincters as far as an SA can. When the coloplasty pouch was compared with the JP in some randomized, controlled trials (RCT), and limited RCT, it showed results comparable to the JP 21,22 and superior to the SA. 23 However, no randomized trial has prospectively compared the functional outcome of all 3 procedures.…”
mentioning
confidence: 99%
“…The exit conduit from the coloplasty reservoir could fit/traverse the anal sphincters as far as an SA can. When the coloplasty pouch was compared with the JP in some randomized, controlled trials (RCT), and limited RCT, it showed results comparable to the JP 21,22 and superior to the SA. 23 However, no randomized trial has prospectively compared the functional outcome of all 3 procedures.…”
mentioning
confidence: 99%
“…It is easier to make and can be located in the pelvic floor even when there is a lot of fatty tissue in the mesocolon. In randomized studies (29,33,58,131 comparing coloplasty with the colon J pouch, no difference was found in the frequency of bowel movement in the early post-operative phase up to eight months, and the same result was seen in three studies up to 18 and 24 months respectively after surgery. In one of the studies (58) an advantage was seen with the colon J pouch with regard to imperative urge to defecate up to eight months post-operatively, however not after a longer period (29,33,131).…”
Section: Coloplasty V Colon J Pouchmentioning
confidence: 77%
“…In randomized studies (29,33,58,131 comparing coloplasty with the colon J pouch, no difference was found in the frequency of bowel movement in the early post-operative phase up to eight months, and the same result was seen in three studies up to 18 and 24 months respectively after surgery. In one of the studies (58) an advantage was seen with the colon J pouch with regard to imperative urge to defecate up to eight months post-operatively, however not after a longer period (29,33,131). In the studies the continence scores and use of antidiarrheals did not differ in the early post-operative period (29,33,58,131), nor in two studies covering a longer period after surgery (29,33,131).…”
Section: Coloplasty V Colon J Pouchmentioning
confidence: 77%
See 1 more Smart Citation
“…Brown, he had the following advantages: compactness, ease of sending down in conditions of small pelvis and in patients with a short mesentery of the colon [30]. However, according to most studies, there was statistically significant differences in functional performance compared with "J" reservoir [38,39].…”
Section: Methods Of Surgical Correction Of Functional Disorders For Pmentioning
confidence: 99%